Peningkatan Pemahaman Peranan Politik Luar Negeri Indonesia Dalam Era Globalisasi Melalui Metode Pembelajaran Kooperatif Model TGT - Ahmad Ro’in (Education Research Center, 2025)
This study explores the effectiveness of implementing the cooperative learning method, Team Games Tournament (TGT), to enhance students' learning achievements and cooperative skills in Class VI-A at SDN 1 Sawahmulya Sangkapura Gresik. Conducted through two cycles of classroom action research, the study reveals a significant improvement in both students' understanding of the subject matter and their social skills, such as communication, collaboration, and mutual assistance within groups. The findings show a substantial increase in the average class score, with a 100% mastery level achieved by all students in the second cycle. The success observed in the second cycle resulted from various improvements made after reflecting on the first cycle’s outcomes, including better motivation strategies, clearer communication of learning objectives, more effective time management, and the use of relevant learning media. The increased active participation of students in the learning process indicates that the TGT method can create a more interactive and collaborative learning environment. Despite the significant improvements, several aspects require further attention to optimize future learning. Teachers need to continuously develop skills to motivate students, provide more guided assistance in concept formulation, and ensure more effective time management to maintain and enhance positive outcomes. The implications of this study are crucial for the field of education. Teachers and educators are encouraged to leverage these findings and adopt more innovative and adaptive approaches, such as TGT, to improve learning outcomes and students’ social skills. Continuous reflection and adjustment of teaching strategies, aligned with classroom conditions and student needs, are key to achieving effective and meaningful learning. Overall, this study contributes to the development of more effective learning practices in primary education and serves as a reference for further research exploring other cooperative learning strategies. Future studies are expected to enrich the literature on cooperative learning methods and help create better and more innovative teaching and learning processes in various educational contexts